2022
DOI: 10.1007/s00401-022-02424-5
|View full text |Cite
|
Sign up to set email alerts
|

ATRT–SHH comprises three molecular subgroups with characteristic clinical and histopathological features and prognostic significance

Abstract: Atypical teratoid/rhabdoid tumor (ATRT) is an aggressive central nervous system tumor characterized by loss of SMARCB1/INI1 protein expression and comprises three distinct molecular groups, ATRT–TYR, ATRT–MYC and ATRT–SHH. ATRT–SHH represents the largest molecular group and is heterogeneous with regard to age, tumor location and epigenetic profile. We, therefore, aimed to investigate if heterogeneity within ATRT–SHH might also have biological and clinical importance. Consensus clustering of DNA methylation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 45 publications
4
14
1
Order By: Relevance
“…This is mostly due to the fact that ATRT has a complex histologic pattern of a combination of rhabdoid, epithelial, primitive neuroepithelial, and mesenchymal components. These histological patterns lead it to be commonly mistaken for medulloblastoma, choroid plexus carcinoma, or CNS primitive neuroectodermal tumor [5]. The ability to diagnose ATRT has only recently been made accessible due to the advent of immunohistochemical testing in the late 1990s [6].…”
Section: Introductionmentioning
confidence: 99%
“…This is mostly due to the fact that ATRT has a complex histologic pattern of a combination of rhabdoid, epithelial, primitive neuroepithelial, and mesenchymal components. These histological patterns lead it to be commonly mistaken for medulloblastoma, choroid plexus carcinoma, or CNS primitive neuroectodermal tumor [5]. The ability to diagnose ATRT has only recently been made accessible due to the advent of immunohistochemical testing in the late 1990s [6].…”
Section: Introductionmentioning
confidence: 99%
“…While we observed consistent drug sensitivity across all screened ATRT-MYC models, ATRT-SHH tumoroid models displayed strong intertumoral differences in drug response. This could be explained by the recent observation that the ATRT-SHH subgroup can be further subdivided into three subgroups with different clinical outcomes [ 39 ]. Drug testing on larger collections of ATRT-SHH tumoroid models will be required to determine whether the observed differences in drug sensitivity are indeed caused by subgroup differences.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, ATRT samples were evaluated from a cohort of 325 patients from the Hospital for Sick Children in Toronto and 65 patients from the Children's Oncology Group (COG) study ACNS0333, and results validated the molecular subgroupings and revealed that the 16% of patients with germline mutations had a 4‐year overall survival (OS) of only 20% 18,19 . There have been conflicting data between the COG study, European Rhabdoid Registry (EU‐RHAB), and St. Jude Children's Research Hospital with regard to whether the ATRT‐SHH 19 or ATRT‐TYR 20,21 subgroup has a better prognosis; recent work demonstrates that ATRT‐SHH may be further subdivided into three molecular subgroups associated with differing OS 22 . As a result, genomic subtyping may be helpful for prognosticating outcomes in RTPS and rhabdoid tumor variants 23,24 …”
Section: Genetic Basis Of Rtpsmentioning
confidence: 99%